A National Early Intervention System as a Strategy to Promote Inclusion and Academic Achievement in Portugal - Franco, Vitor; Melo, Madalena; Santos, Graça; Apolónio, Ana; Amaral, Leonor (Frontiers in Psychology, 2017)
Early intervention with children at risk or facing developmental problems is a practice defined by three fundamental characteristics: being family-centered, being based on the community and on the child's life context, and being conducted by a team with transdisciplinary practice. In this paper we wish to present how the SNIPI-National System of Early Intervention, implemented in Portugal over the past 15 years, contributes to promote maximum development and the full inclusion of children up to 6 years of age and works to prevent school failure. The SNIPI covers the entire territory and intends to respond to the needs of children with developmental disorders or those in at risk situations. This community-based early intervention model is linked to the health, education and social care systems, involving the three responsible Ministries. In the present community case study, we present the implementation of this program in the Alentejo region, involving 31 local teams and almost 2500 children. Through the regional structure’s reports and the responses of parents and professionals in impact studies, we demonstrate how the system is established and how it tackles school failure and improves the educational inclusion of these children. The impact of this Early Intervention model has been significant not only on children's developmental outcomes, but also for the health, education and social care professionals who work in a transdisciplinary perspective, as well as for the families who became more skilled at evaluating the children´s needs and the support provided. This approach to implementing a family-centered Early Intervention program can contribute to full inclusion. It facilitates the transition to schooling based on a non-discriminatory approach and educational achievement by aiding development and an adapted contextualization in pre-school education. This program system introduces significant innovation within the framework of existing educational policies that promote development and inclusion, and has therefore earned the interest of the scientific community and policy-makers alike. It has been possible to implement some of principles already studied but it had never been tested.